X-ray-activated nanosystems for theranostic applications - Chen, Xiaofeng; Song, Jibin; Chen, Xiaoyuan; Yang, Huanghao (Chemical Society reviews, 2019)
X-rays are widely applied in clinical medical facilities for radiotherapy (RT) and biomedical imaging. However, the sole use of X-rays for cancer treatment leads to insufficient radiation energy deposition due to the low X-ray attenuation coefficients of living tissues and organs, producing unavoidable excessive radiation doses with serious side effects to healthy body parts. Over the past decade, developments in materials science and nanotechnology have led to rapid progress in the field of X-ray-activated tumor-targeting nanosystems, which are able to tackle even systemic tumors and relieve the burden of exposure to large radiation doses. Additionally, novel imaging contrast agents and techniques have also been developed. In comparison with conventional external light sources ( e.g. , near infrared), the X-ray technique is ideal for the activation of nanosystems for cancer treatment and biomedical imaging applications due to its nearly unlimited penetration depth in living tissues and organisms. In this review, we systematically describe the interaction mechanisms between X-rays and nanosystems, and provide an overview of X-ray-sensitive materials and the recent progress on X-ray-activated nanosystems for cancer-associated theranostic applications. We systematically provide an overview of X-ray-sensitive materials and the recent progress on X-ray-activated nanosystems for cancer-associated theranostic applications.